Levirate in Ancient Israel: Overlapping Frames with Early Indian Practice of Niyoga - Sahgal, Smita (Advances in Social Sciences Research Journal, 2018)
Surrogacy was a well-known practice in ancient societies. Its application was rare but mandated when the matter of threatened lineage surfaced. Since very early times and particularly within patriarchal societies, sons were regarded as natural inheritors of property, holders of lineage and on many occasions performers of rites for ancestors. Hence, the absence of a male issue was viewed as a solemn social anomaly. Corrective solutions had to be worked out and many ancient societies came up with their alternative paradigms. In ancient Israel the practice of yibbum emerged and ensured lineage continuity. Its ancient Indian counterpart was the practice of niyoga that came under what is largely understood as apaddharma or the law of exigency. In both societies childless widow/wife was made to cohabit with a man, generally from within the family and the son produced furthered the lineage of her husband. The consent of the widow/wife was not really sought for the practice to get its social sanction. In the paper we shall study the issue from a gendered perspective and explore whether the practices of Yibbum and Niyoga implied exploitation of women. Further what was the class and caste location of the practice respective cultures and who eventually stood to benefit from it in two different parts of ancient world.